Epidemiology Profile of Viral Meningitis Infections Among Patients in Qatar (2015–2018) - Mathew, Shilu; Al Khatib, Hebah A.; Al Ansari, Khalid; Nader, Joanne; Nasrallah, Gheyath K.; Younes, Nadin N.; Coyle, Peter V.; Al Thani, Asmaa A.; Al Maslamani, Muna A.; Yassine, Hadi M. (Frontiers in Medicine, 2021)
Background: Little is known about the etiology of meningitis in the MENA region, including Qatar. Viral agents are considered the major cause for meningitis worldwide. Here, we present primary data about the etiology and clinical and demographic characteristics of viral meningitis (VM) in Qatar between 2015 and 2018. Methods: We retrospectively collected data from Hamad Medical Corporation (HMC), which provides about 80% of healthcare services in Qatar. Data were collected for the period between 2015 and 2018. During this time period, 6,705 specimens were collected from patients with suspected meningitis attending HMC and primary healthcare centers. These specimens were tested for a panel of viruses using the “FTD Viral meningitis” multiplex real-time PCR kit that detects Adenovirus (ADV), Human herpesvirus 1&2 (HSV1 and HSV2), Epstein–Barr virus (EBV), Enteroviruses (EV), Cytomegalovirus (CMV), Varicella zoster virus (VZV), and Parechovirus (PV). Results: Only 10.9% (732/6,705) of all suspected meningitis cases were caused by viral agents. 60.9% of the reported cases were males, compared to 39.1% in females. Most of the infections (73.9%) were reported in children younger than 10 years of age. EV were identified as the main causative agent (68.7%), followed by EBV (7.5%) and ADV (6.8%). Other viral agents including VZV, PV, HSV-1, and HSV-2 were also detected with a lower frequency. Confirmed VM were more prevalent among Qatari subjects compared to other nationalities. We observed no specific seasonality of viral agents, but a slight rise was recorded during the spring seasons (March to June). Fever (59.4%, 435/732) and acute central nervous system (CNS) infection (15.6%, 114/732) were initial symptoms of most cases. Conclusion: This is the first report about the molecular epidemiology of VM in Qatar. In line with the international records, our data showed that EV is responsible for 68.7% of Qatar's VM cases. Further studies are needed to genotype and serotype the identified viruses.